The economics of friendship : conceptions of reciprocity in classical Greece - Berkel, Tazuko Angela van, 1979- (Studies in Critical Social Sciences;, 2020)
In The Economics of Friendship, Tazuko Angela van Berkel offers an account of the notion of reciprocity in 5th- and 4th-century Greek incepting social theory. The preoccupation with the norms of philia and charis, conspicuous in sources from the Classical Period, is a symptom of changes in the shape of ancient economic activities: the ubiquitous norm that one should reciprocate benefit with benefit becomes a source of conceptual confusion in the Classical Period, where other forms of exchange become conceptually available. This confusion and tension between different models of mutuality, is productive: it is the impetus for folk theory in comedy, tragedy and oratory, as well as philosophical reflection (Xenophon, Plato, Aristotle) on what it is that binds people together.